On ρ−statistical convergence of order α of sequences of function - Nazlım Deniz Aral; Hacer Şengül Kandemir; Mikail Et (E-Journal of Analysis and Applied Mathematics)
In this study, by using definition of ρ-statistical convergence which was defined by Çakallı, we introduce the concepts of pointwise wαρ (f )-summability, pointwise ρ-statistical convergence of order α and uniform ρ-statistical convergence of order α sequences of real-valued functions. Also, we give some inclusion relations between these concepts.